Brand Trust in Driving Brand Loyalty and Purchase Intention in the Digital Streaming Era: A Systematic Literature Review - Muchammad Chusnul Akrom (Indonesian Scientific Publication, 2025)
Brand trust plays a strategic role in shaping long-term consumer relationships in digital streaming services, where user interactions are primarily virtual and consumers constantly face competing content choices. This study synthesizes recent empirical research to develop an integrative framework positioning brand trust as a mediating construct that links consumer engagement strategies with behavioral outcomes such as brand loyalty and purchase intention. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol, analyzing 34 peer-reviewed open-access articles published between 2015 and 2025, selected from the ScienceDirect database through a refined Boolean search process. Thematic analysis revealed that antecedents such as content marketing quality, perceived brand authenticity, social media interaction, and user-generated content (UGC) play a significant role in trust formation. Emotional drivers like brand love and perceived sincerity enhance psychological attachment, while technological features including AI-based personalization, live streaming, and immersive metaverse experiences foster trust when implemented with ethical clarity. Cultural and demographic factors were also identified as important variables, indicating that trust formation is context-sensitive and non-universal. The proposed framework offers both theoretical contribution and practical relevance by demonstrating that brand trust operates not merely as a result, but as a dynamic strategic lever in digital consumer behavior. By integrating emotional, functional, and technological dimensions, the framework underscores the multidimensional nature of trust-building in platform-mediated environments. The study concludes by calling for further empirical validation across various streaming contexts to strengthen brand management strategies